2019
DOI: 10.32628/ijsrset196146
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Traffic Management System Using IoT and Machine Learning

Abstract: India is a developing country. Increase in personal vehicles comes with the development of a country parallely. This has led to rise in congestion in large cities. So, we need a better traffic management system. The purpose of this project is to create a traffic system which is adaptive to the present traffic scenario in a lane. Usually, we have fixed average waiting time for all lanes. This project suggests to change the average waiting time by monitoring the number of vehicles in a lane. The data will be sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Smart algorithms are currently helping many organizations in the private and public sectors to improve their operating efficiencies [57]. In the public sector, for instance, city traffic management can be improved significantly by availing of an adaptive AI-based traffic management system [58]. Strategic placement of sensors closes to street lamps/ bulbs in public spaces facilitates data gathering.…”
Section: Artificial Intelligence In Smart Citiesmentioning
confidence: 99%
“…Smart algorithms are currently helping many organizations in the private and public sectors to improve their operating efficiencies [57]. In the public sector, for instance, city traffic management can be improved significantly by availing of an adaptive AI-based traffic management system [58]. Strategic placement of sensors closes to street lamps/ bulbs in public spaces facilitates data gathering.…”
Section: Artificial Intelligence In Smart Citiesmentioning
confidence: 99%
“…This work's follow-up research aims to more thoroughly analyze traffic monitoring video data and to offer helpful traffic travel advisory services [10]. With a software system, the circumstances of an accident can be determined by identifying overlapping images in real-time video streaming [129]. To create various condition-specific datasets for model testing, we advise a more thorough comparison of these two, employing field data for model calibration, simulation, DTW, and SVM.…”
Section: Recent Trends Research Directions and Lessons Learnedmentioning
confidence: 99%
“…Throughout any trip, there is a chance for accident happening at any moments [2]. Manual control of traffic, by traffic officers or using predefined timers has been confirmed that it's not an real solution to all the earlier cited problems caused by traffic accidents [3]. So we need to design better traffic management system can detect the accident and decreased the severity of injures after an accident by reducing the period gap between the accident happening and the therapeutic response.…”
Section: Introductionmentioning
confidence: 99%